The Impact of Live Streaming of Fresh Agricultural Products on Consumers' Purchase Intention-Consider the Regulatory Role of Policy Support - Sun, Fan (Journal of Global Economy, Business and Finance, 2024)
To understand the influence of fresh agricultural products online live on consumer purchase intention, based on SOR (Stimuli-Organism-Response) theory framework, with convenience, interactivity, anchor prestige, task fit as a stimulus variable, to customer participation as a psychological latent variable construction theory model, based on the questionnaire data, using the structural equation model of measurement model consistency, reliability, convergence validity and validity test, and explore the role of the latent variables, with path coefficient as an observation index analysis of the model results. The research results show that convenience, interactivity, anchor reputation and task fit have significant positive effects on customer participation, among which the biggest influence is convenience; in the process of convenience and interaction on customer participation, policy support plays a positive regulating role, in the process of anchor reputation and task fit on customer participation.